Analysis on the Nature, Functions, and Process of Research: Revealing the Characteristics of Scientific Research, Types of Research, and Classification in Research - Yusawinur Barella; Ana Fergina; Muhammad Khalifa Mustami; Ulfiani Rahman (Universitas Muhammadiyah Enrekang, 2023)
This research article explores the essence, functions, and process of research, with a specific focus on scientific research. In addition, it delves into the characteristics of scientific research, identifies different types of research, and examines classifications within the research field. The aim of this study is to provide a comprehensive understanding of research and its significance in the realm of science and technology. By addressing these aspects, the research aims to deepen readers' knowledge and promote the correct execution of research methodologies. Ultimately, this analysis contributes to the advancement of science and technology by fostering credible and impactful research.